2020
DOI: 10.1097/md.0000000000022452
|View full text |Cite
|
Sign up to set email alerts
|

Complete monoplegia due to limb-kinetic apraxia in a patient with traumatic brain injury

Abstract: Rationale: Limb-kinetic apraxia (LKA) is a disorder of movement execution that is a result of injury to the corticofugal tracts (CFTs) from the secondary motor area. We report on a patient with traumatic brain injury (TBI) and complete monoplegia due to LKA, which was mainly ascribed to injury of the CFT from the secondary motor area using diffusion tensor tractography. Patient concerns: A 35-year-old male was struck by a car from the side during riding an autocycle and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 20 publications
(12 reference statements)
1
26
0
Order By: Relevance
“…On the other hand, the doses of dopaminergic drugs did not appear to be sufficient for resolving LKA compared to the higher doses of dopaminergic drugs prescribed in previous studies. [ 11 , 22 26 ] Second, he could walk without collapse of the hip joint during the stance phase of gait, even though the affected hip extensor muscles did not show sufficient muscle power to maintain the hip joint during the stance phase on physical examination, which is additional evidence of LKA. This patient did not exhibit muscle power of the affected hip joint due to LKA, even though he had sufficient muscle power to maintain the hip joint during the stance phase of gait.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the doses of dopaminergic drugs did not appear to be sufficient for resolving LKA compared to the higher doses of dopaminergic drugs prescribed in previous studies. [ 11 , 22 26 ] Second, he could walk without collapse of the hip joint during the stance phase of gait, even though the affected hip extensor muscles did not show sufficient muscle power to maintain the hip joint during the stance phase on physical examination, which is additional evidence of LKA. This patient did not exhibit muscle power of the affected hip joint due to LKA, even though he had sufficient muscle power to maintain the hip joint during the stance phase of gait.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Several studies have reported patients who showed motor recovery by the resolution of LKA in patients with brain injury. [ 11 , 22 26 ] In contrast, little is known about delayed gait recovery due to LKA resolution. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic Brain Injury (TBI) is the direct or indirect effect of external force on the head, causing mechanical damage to the brain tissue, and a series of secondary pathological injuries. It can have different clinical manifestations, such as changes in brain morphology, limb dysfunction ( Jang and Seo, 2020 ), endocrine changes ( Li and Sirko, 2018 ), abnormal blood coagulation ( Albert et al, 2019 ), mental disorders ( Pavlovic et al, 2019 ), and changes in consciousness. Its disability rate and death rate are the highest among limb injuries, costing hundreds of billions of dollars each year ( Rubiano et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…A diagnosis of LKA is clinically important because the treatment strategy differs according to whether the motor weakness is ascribed to a CST injury or LKA. In particular, recent studies reported that dopaminergic agonists are effective for improving LKA [ 2 , 12 19 ]. On the other hand, a precise diagnosis of LKA is often limited because it is made based on clinical observation of the movement characteristics with a confirmation of the CST state, and no specific clinical assessment tools for LKA have been developed [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Classically, LKA is considered based on the condition of intactness of the affected CST. However, recent studies reported that the patients who had injury of the CST presented with LKA [ 15 , 16 , 19 , 23 ]. Therefore, a precise diagnosis of LKA can be limited in patients who cannot execute movements due to severe weakness caused by the partial injury of the CST combined with LKA [ 15 , 16 , 19 , 23 ].…”
Section: Introductionmentioning
confidence: 99%